The Influence of Population and Government Expenditure on Surakarta City Original Revenue 2006-2023 - Fahnur Ari Wijaya; Kukuh Arisetyawan; Ladi Wajuba Perdini Fisabilillah; Risqi Noor Hidayati Putri (Universitas Nusantara PGRI Kediri, 2024)
One of the problems that still occurs in the region until now is the problem of regional finance. This study aims to determine whether population and government expenditure have an influence on local revenue in Surakarta City in 2006-2023. This study uses an associative quantitative approach and the method used is multiple linear regression processed with the help of STATA 13. The results showed that population and government expenditure have a positive and significant effect on local revenue. Simultaneously, both variables have a significant effect on local revenue in Surakarta City.